Differentially Expressed Bone Marrow microRNAs Are Associated With Soluble HLA-G Bone Marrow Levels in Childhood Leukemia - Almeida, Renata Santos; Gomes, Thailany Thays; Araújo, Felipe Souza; Oliveira, Sávio Augusto Vieira de; Santos, Jair Figueredo; Donadi, Eduardo Antônio; Lucena-Silva, Norma (Frontiers in Genetics, 2022)
HLA-G is a non-classical histocompatibility class I molecule that plays a role in the immune vigilance in cancer and infection diseases. We previously reported that high soluble HLA-G (sHLA-G) levels in bone marrow were associated with high blood cell count in T-acute lymphoblastic leukemia, a marker associated with a poor prognosis. To understand leukemia's posttranscriptional HLA-G gene regulation, we evaluated the bone marrow microRNA profile associated with the HLA-G bone marrow mRNA expression and with sHLA-G bone marrow levels in children exhibiting acute leukemia (B-ALL, T-ALL, and AML), using massively parallel sequencing. Ten differentially expressed miRNAs were associated with high sHLA-G bone marrow levels, and four of them (hsa-miR-4516, hsa-miR-486-5p, hsa-miR4488, and hsa-miR-5096) targeted HLA-G, acting at distinct HLA-G gene segments. For qPCR validation, these miRNAs expression levels (ΔCt) were correlated with HLA-G5 and RREB-1 mRNA expression and sHLA-G bone marrow levels according to the leukemia subtype. The hsa-miR-4488 and hsa-miR-5096 expression levels were lower in B-ALL than AML, while hsa-miR-486-5p was lower in T-ALL than AML. In T-ALL, hsa-miR-5096 correlated positively with HLA-G5 and negatively with sHLA-G. In addition, hsa-miR-4516 correlated negatively with sHLA-G levels. In AML, hsa-miR-4516 and hsa-miR-4488 correlated positively with HLA-G5 mRNA, but the HLA-G5 negatively correlated with sHLA-G. Our findings highlight the need to validate the findings of massively parallel sequencing since the experiment generally uses few individuals, and the same type of leukemia can be molecularly quite variable. We showed that miRNA's milieu in leukemia's bone marrow environment varies according to the type of leukemia and that the regulation of sHLA-G expression exerted by the same miRNA may act by a distinct mechanism in different types of leukemia.